Case Studies in Adapted Physical Education Empowering Critical Thinking. - Hodge, Samuel R.; Murata, Nathan M.; Block, Martin E., 1958-; Lieberman, Lauren J., 1965- (Milton : Routledge, 2019)
Covering self-contained adapted physical education classes, general physical education programs, and youth sports and community recreation, this book presents a series of case studies of teaching individuals of varied ability and disability in physicalactivity settings. Outlining realistic scenarios, it encourages an interactive, problem-solving teaching and learning style and the development of critical thinking skills. Now in a fully revised and updated second edition, the book covers a wide range of different professional issues, themes, disabilities, and conditions, from assessment and behavior management processes to working with students with intellectual disabilities, motor difficulties, chronic illness, or obesity. Each case study includes questions that challenge the reader to ref lect on the practical issues involved and how to build inclusive teaching strategies. This book is valuable reading for all physical education students, teacher candidates, and novice and experienced teachers looking to deepen their understanding of adapted physical education and to improve their professional practice. It is an essential companion to any adapted physical education or physical activity course.
Description based upon print version of record.
Keywords: Physical education for children with disabilities -- Study and teaching -- Case studies; Coaching (Athletics).; School sports; Physical education for children with mental disabilities -- Study and teaching -- Case studies